Hippocampal sparing approach in fractionated stereotactic brain VMAT radio therapy: A retrospective feasibility analysis. (10th November 2017) - Daniela Falco, Maria; Giancaterino, Stefano; D'Andrea, Marco; Gimenez De Lorenzo, Ramon; Trignani, Marianna; Caravatta, Luciana; Di Carlo, Clelia; Di Biase, Saide; Allajbej, Albina; Genovesi, Domenico
Abstract: Volumetric Modulated Arc Therapy (VMAT) techniques for fractioned stereotactic brain radiotherapy (FSBRT) can achieve highly conformal dose distribution to intracranial lesions. However, they can potentially increase the dose to hippocampus (H) causing neurocognitive toxicity during the first four months after irradiation. The purpose of this study was to assess the feasibility of hippocampal‐sparing (HS) treatment plans in 22 patients with brain metastasis treated with VMAT technique. Firstly, we retrospectively analyzed hippocampal doses in all 22 VMAT original (not hippocampal‐sparing, NHS) plans. Plans with hippocampal dose exceeding constraints (9 out of 22) were re‐planned considering dose constraints on the hippocampus (H) and on hippocampal avoidance zone (HAZ) generated using 5 mm isotropic margin to the hippocampus. Conformity (CI) and homogeneity indexes (HI) on the target and MUs, were maintained as close as possible to the original plans. Mean CINHS and CIHS obtained were: 0.79 ± 0.11 and 0.81 ± 0.10, respectively ( P = 0.75); mean HINHS and HIHS were 1.05 ± 0.02 and 1.04 ± 0.01 respectively ( P = 0.72). In both sets of plans, the mean MU values were similar: 1033 ± 275 and 1022 ± 234 for NHS and HS respectively. In HS plans, the mean hippocampal dose was decreased by an average of 35%. After replanning, the Dmax (21.3 Gy) for HAZ and H was met by 45% (4/9) and 78% (7/9) of the NHS plans, respectively. The worst results were obtained for cases with target volumes extention closer than 12 mm to H, because of the difficulty to spare hippocampus without compromising target coverage. After replanning D40% constraint value (7.3 Gy) was met by all the 9 NHS plans. In conclusion, this study suggests that an hippocampal‐sparing approach to FSBRT is feasible resulting in a decrease in the dose to the hippocampus without any loss in conformity or increase in treatment time.